2013
DOI: 10.1186/1471-2148-13-168
|View full text |Cite
|
Sign up to set email alerts
|

The Fukushima nuclear accident and the pale grass blue butterfly: evaluating biological effects of long-term low-dose exposures

Abstract: BackgroundOn August 9th 2012, we published an original research article in Scientific Reports, concluding that artificial radionuclides released from the Fukushima Dai-ichi Nuclear Power Plant exerted genetically and physiologically adverse effects on the pale grass blue butterfly Zizeeria maha in the Fukushima area. Immediately following publication, many questions and comments were generated from all over the world. Here, we have clarified points made in the original paper and answered questions posed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
89
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(102 citation statements)
references
References 92 publications
7
89
1
Order By: Relevance
“…Another study indicated a high incidence of morphological abnormality in gall-forming aphids14. Consistent with these studies, we have demonstrated that the Japanese pale grass blue butterfly, Zizeeria maha ( Yamato shijimi in Japanese), was affected physiologically and genetically in the polluted area, likely due to the artificial radionuclides released from the Fukushima Dai-ichi NPP1516. In one of a series of experiments, we have shown a decrease in the survival rate of this butterfly in accordance with the level of radioactivity of cesium in the diet (i.e., the leaves of the host plant, Oxalis corniculata )1516 under our standard rearing conditions17.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Another study indicated a high incidence of morphological abnormality in gall-forming aphids14. Consistent with these studies, we have demonstrated that the Japanese pale grass blue butterfly, Zizeeria maha ( Yamato shijimi in Japanese), was affected physiologically and genetically in the polluted area, likely due to the artificial radionuclides released from the Fukushima Dai-ichi NPP1516. In one of a series of experiments, we have shown a decrease in the survival rate of this butterfly in accordance with the level of radioactivity of cesium in the diet (i.e., the leaves of the host plant, Oxalis corniculata )1516 under our standard rearing conditions17.…”
supporting
confidence: 86%
“…We found that the levels of ingested cesium from the 4 localities (i.e., Hirono, Fukushima, Iitate-flatland, and Iitate-montane) were much higher than that from Ube, a control locality; thus, it is not surprising that harmful biological effects were clearly detected in previous studies1516. However, we do not know if our results can be directly compared to other studies on natural radiation or other nuclear accidents.…”
Section: Discussioncontrasting
confidence: 62%
“…In a rebuttal Hiyama et al . [10] provided extensive evidence that supports their initial conclusions (Table 2). In particular, they have shown five important findings: the color patterns obtained in Fukushima differed from color patterns produced by aberrant temperatures and sibling crosses; the minor morphological abnormalities were not present at high frequency in Fukushima before the accident, as shown by older specimens in collections; the abnormal traits were heritable; mutation accumulation occurred from May to September 2011; and finally, positive controls produced normal adults.…”
Section: Levels Of Scientific Scrutinysupporting
confidence: 56%
“…Although the IAEA generally assumes limited impacts to organisms from dose rates B50 lGy h -1 , there is considerable discussion of these arbitrary thresholds given the lack of sufficient information concerning unknown individual and species variation in sensitivity, the role of multigeneration exposures, and the importance of complex community interactions in determining individual-, population-, and ecosystem-level responses to radiation sources. Recent analyses of organisms inhabiting Chernobyl, Fukushima, and other naturally radioactive regions around the world point to measurable, biologically significant impacts at what are much lower dose rates than those recommended by IAEA (e.g., Mousseau 2009, 2015;Hiyama et al 2012Hiyama et al , 2013Yamashiro et al 2013;Møller et al 2014). Clearly, further research is needed.…”
Section: Resultsmentioning
confidence: 99%